(untitled) (Colloquia Comparativa Litterarum, 2025)
This article is an introduction to the close reading of Victor Pelevin’s novel Journey to Eleusis (2023) as a paradigmatical example of the Russian dystopian literature from the beginning of the 21th century. Journey to Eleusis is the final part of a trilogy whose previous installments include the collection of short novels Transhumanism Inc. (2021) that set the dystopian universe, and the sequel KGBT+ (2022) taking place already in the wartime sociopolitical reality. I argue that starting with Vladimir Sorokin’s Blue Lard (1999) the contemporary Russian dystopia intertwines idiosyncratically futurism and archaism into a retro-dystopian frame, which I discern in Pelevin’s trilogy. As I view it, this specific dystopian blend aims at the representation of a history of the present of the Putin era with its neo-totalitarian version of the Russian imperial concept of the “Third Rome” which is crucial to Journey to Eleusis.